Weak-form efficiency of foreign exchange market in the organisation for economic cooperation and development countries: unit root test - Juliana, Ibrahim; Hartini, Ab Ghani; Safrul Izani, Mohd Salleh; Yasmiza, Long (2011)
This paper will look at the weak-form efficiency of the foreign exchange market in thirty (30) Organization for Economic Cooperation and Development (OECD) countries. We employ Augmented Dickey-Fuller (ADF), Philip-Perron (PP) and Kwiatkowski-Phillips-Schmidt-Shin analysis to examine for the unit root. Using weekly data for the period 2000 to 2007, the results for weak-form efficiency using ADF and PP tests indicate that the exchange rates studied follow random walks. The current value of the exchange rate cannot be predicted using its past values. In addition, the OECD foreign exchange market consistent with the weak-form of the Efficient Market Hypothesis.